Leveraging Material Properties in Fluorescence Anion Sensor Arrays: A General Approach. Issue 26 (13th May 2013) - Anzenbacher, Pavel; Liu, Yuanli; Palacios, Manuel A.; Minami, Tsuyoshi; Wang, Zhuo; Nishiyabu, Ryuhei
Abstract As the demand for probes suitable for sensor development increases, investigation of approaches that utilize known successful receptors gains in general importance. This study describes a two‐prong approach that can be used as a guide to developing sensors from known receptors. First, the conversion of a simple receptor, calix[4]pyrrole, into a fluorescent probe to establish a ratiometric signal is described. Secondly, the sensors that employ an output from a single ratiometric calix[4]pyrrole probe are fabricated by using poly(ether‐urethane) hydrogel copolymers. These hydrogels are designed to absorb, internalize and transport aqueous electrolytes. A sensor array of ten different poly(ether‐urethane) matrices with varying comonomer proportions were doped with a single probe and were exposed to eight different anions: acetate, benzoate, fluoride, chloride, phosphate, pyrophosphate, hydrogen sulfide, and cyanide, eight urine samples and anti‐inflammatory drugs (NSAIDs). The poly(ether‐urethane) matrices comprise different proportions of anion‐binding urethane moieties and different hydrophilicity given by the ratio between ethylene glycol ether and butylene glycol ether. This diversity in the hydration behavior provides different environment polarity, in which the recognition and self‐assembly processes display enough diverse behavior to allow for unique response of the probe to the analytes. Furthermore, a single probe is shown to recognize eight different aqueous anions and eight urine samples when embedded in ten different polyurethanes in an array that displays 100 % classification accuracy. To demonstrate the potential of the concept for quantitative studies, an estimation of non‐steroidal anti‐inflammatory drugs ibuprofen and diclofenac in water and in saliva was performed. A limit of detection of 0.1 ppm and a dynamic range of 0.1–0.6 and 0.05–60 ppm was observed, respectively. Given the general difficulty of chemosensors to recognize aqueous anions, the fact that one probe recognizes eight different analytes attests to an enormous effect of the polymer environment on the recognition process. This method could be used to generate a variety of sensor arrays for various analyses including species that are difficult to recognize, such as small‐molecule‐ and inorganic anions.